2013
DOI: 10.5336/medsci.2012-29432
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Polycythemia May be Free of JAK2V617F Mutation

Abstract: A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : Polycythemia is known as increased erythrocytosis and is linked to the erythropoiesis cascade including erythropoietin, erythropoietin receptor and intracellular signaling proteins. The Janus kinase 2 (JAK2) is the key signal transducer in the erythropoiesis cascade. A function gain mutation (V617F) at JAK2 gene has been identified in polycythemia vera in adults. On the other hand, the molecular etiology of neonatal polycythemia has not been elucidated we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 16 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…However, a few studies suggest that JAK2V617F mutation may not be the initiator of the disease [ 20 ]. It is considered to be a late genetic event occurring in patients with myeloproliferative disease, as reported in our recent studies [ 21 , 22 , 23 ]. The role played by free radicals in causing DNA damage and the pathways of cellular oxidative damage in neoplastic transformation have been well defined [ 24 ].…”
Section: Discussionmentioning
confidence: 90%
“…However, a few studies suggest that JAK2V617F mutation may not be the initiator of the disease [ 20 ]. It is considered to be a late genetic event occurring in patients with myeloproliferative disease, as reported in our recent studies [ 21 , 22 , 23 ]. The role played by free radicals in causing DNA damage and the pathways of cellular oxidative damage in neoplastic transformation have been well defined [ 24 ].…”
Section: Discussionmentioning
confidence: 90%
“…Polycythemia Vera, presented in our patient, is a myeloproliferative disorder of bone marrow that red blood cells are produced in large amounts. PV is seen in older ages particularly under the effect of acquired somatic mutation of JAK2 (V617F) 14,15 that the latter is a diagnostic parameter of the disease. 16 JAK2 is a member of the Janus kinase family of nonreceptor protein tyrosine kinases and has an important role in the cellular development and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Suggestion of a possible role of JAK2 mutations in lentiginosis syndromes with a single case of a patient with multiple lentigines and concomitant diagnosis of polycythemia vera (PV), might be thought as a 'fatal flaw' in the first encounter since JAK2 activating mutations such as V617F in PV are not germline mutations, 14 but rather somatic ones -which supposed to occur only in myeloid haematopoietic progenitors/stem cells; 25 however in our case, surprisingly the cells comprising the skin lentigines of the reported patient do carry the JAK2V617F mutation (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that there is a mutation that causes;true polycythemia vera disease, which occurs in a gene called (The Janus kinasez "JAK" 2),in exon 14 of chromosome 9, and this mutation was;discovered in approximately 95% of patients with .polycythemia vera and about 50% of people with Essential thrombocytosis and primary; myelofibrosis (2) .…”
Section: A Primary Polycythemia (Polycythemia Vera)mentioning
confidence: 99%
“…Polycythemia is a Greek term synonymous with Erythrocytosis,and literally translates to many cells in the blood (2) . Polycythemia is an uncommon clinical discovery, and one of its most important features is an increase in the number of red blood cells, as well as an increase in the concentration of hemoglobin (Hb) .and packed cell volume (PCV) (3,4) .…”
Section: Introductionmentioning
confidence: 99%